Computational Behavior of Trihybrid Casson Nanofluid Blood Flow Occurring Inside the Conical Gap Between the Rotating Disk and the Cone (Contemporary Mathematics, 2024)
The investigation of the flow patterns of a trihybrid nanofluid flow situated in the conical gap that is created among a revolving disc and a stationary cone computationally examined in this study. Three different types of nanoparticles, Al2O3, TiO2 and Ag are examined with blood as the base fluid according to flow properties and energy phenomenon. While discussing the heat transfer mechanism in trihybrid nanofluid flow crossing through the disc and cone, four different types of cases are explored likewise the disc and cone may be rotating at the same rate or at different rates, or one may be stationary about the other. The numerical scheme is planted to observe the fluid flow and heat transfer patterns. In the current article, we investigated rheological parameters, including rotating speed, cone angle, and concentration of nanoparticles, and the effect of heat transfer performance over velocity and temperature patterns. The results shed light on the complex interactions between the geometric and nanofluid characteristics, providing useful information for fluid dynamics and thermal management applications. This fluid model is also useful for the study of blood pressure, arthritis, brain therapy, and malignant tumors. The graphs are plotted using the MATLAB program BVP4C to ensure convergence. Several variables, such as a magnetic parameter, Prandtl's number, and Reynold's number, have an impact on temperature and velocity profiles. It is evident that the amalgamation of the fraction of three nanoparticles reduces the velocity and enhances the temperature of the nanofluid. The momentum boundary layer expands when the cone and disc rotate in the same direction.
Keywords: trihybrid nanofluid; magnetohydrodynamics; cone; rotating disk; blood flow